Islam Madzhab Indonesia (Menelisik Karakteristik Bangunan Fiqh Khas Keindonesiaan) - Mustatho Mustatho (Al-Rabwah, 2020)
Fiqh Keindonesiaan is an effort of the embodiment of Islamic Law with the cultural context and personality of the nation. Fiqh Keindonesiaan meniscaya exist for two reasons, the first time and place of different implementation between Indonesia and other Islamic centers. Secondly, the reason that every place has customs and customs varies according to the socio-anthropological and socio-political tendencies of each place; kaedah which reinforces this reason is "taqhayyurul ahkam bi taqhayyiril azlam wa makan". Besides the difference of place and time, differences of customs have their own historical and historical backdrops. The Kaedah is "al-'adaat al-Muhakamaat". While the historical backdrops are different experiences and different legal decisions among the Imams of the madhhab, for example the Hanafi Hanafi in Kuffah, Maliki in Madinah, Shafi'i in Baqdad and Egypt (qaul qadim, and jadid), and the Hambali school of Baghdad. Also fiqh madzhab Indonesia has its locality with a different system with other contemporary community system.Efforts to support the emergence of fiqh Keindonesiaan can be started by growing Ushul Fiqh Keindonesiaan unique. The framework of the method of ushul fiqh keindonesiaan ditumpukan to the practice of al-Urf and maslahah which can become the rest of the law. Meanwhile, the operationalization of fiqh keindonesiaan is an effort to study different cases in Indonesia with other legal cases that have existed in the Islamic world with a way through ijtihad fardi and ijtihad jama'i by every expert and ulul amri in Indonesia by applying the ushul framework of fiqh itself. So fiqh keindonesiaan is not an illusion, but he can be Real.